Writing training materials that work how to train anyone to do anything : a practical guide for trainers based on current cognitive psychology and ID theory and research - Foshay, Wellesley R., 1947-; Silber, Kenneth H.; Stelnicki, Michael B., 1939-; Safari eBooks (San Francisco : Jossey-Bass/Peiffer, 2003)
"The explosion of e-learning has attracted huge numbers of practitioners to the field of instructional design (ID), many with little or no actual ID training. Writing Training Materials that Work is different. In it, the authors identify, synthesize, and summarize the most current best practices in ID. They offer new ways of teaching declarative knowledge (facts, concepts, and principles) and well- to ill- structured procedural knowledge (problem solving). Their recommendations are based on those principles in the cognitive learning and instruction literature that are internally consistent, prescriptive, and have been empirically demonstrated to make a cost-effective difference. The authors' approach is easy to implement and consistently gets results because it focuses on teaching deep understanding and problem-solving, allowing learners to generalize and transfer learning to new situations without re-training"--Resource description page.
The cognitive approach to training development -- A cognitive training model -- How to begin any lesson : the first three elements -- How to organize and present information : message design principles -- Teaching facts -- Teaching concepts -- Teaching principles and mental models -- Teaching well-structured problem-solving -- Teaching ill-structured problem-solving -- Teaching troubleshooting -- Teaching complete lessons -- Issues underlying the cognitive approach to instructional design -- Issues underlying teaching declarative knowledge -- Issues underlying teaching procedural knowledge.
Description based on print version record.
Includes bibliographical references (p. 237-239) and index.
Keywords: Employees -- Training of; Training manuals; Electronic books